Pengelolaan Sampah Sebagai Implementasi Ekonomi Kreatif Melalui Program Clean And Cash Upaya Menjaga Pencemaran Lingkungan - Rohmaniyah Rohmaniyah; Nurul Alfian; Devi Lestari Pramita Putri; Subhan Subhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Waste is a problem of the environment and urban communities that until now has no solution. Waste Bank is an alternative to reduce waste production because it directly involves the community. Through this Waste Bank program not only involves the community in the implementation process but can improve the community's perspective on waste management. The implementation of this service begins with providing teaching material to the community so that they are motivated to be able to sort household waste and together form a waste bank as a means of channeling waste. The counseling with material about the importance of managing waste with waste banks and how waste banks work. The result of this training is that the community is very enthusiastic to participate in the waste management program through the clean and cash program because the clean amd cash program is considered an effective program by the community in addition to reducing the effects of environmental pollution from garbage collectors also get money exchanged to the garbage bank. This craft training also adds to the community's insight to utilize used goods into things that are valuable and can be resold.